Modelagem computacional das reações dos Ânions OH- e CH3O- com o nitrito de metila em fase gasosa - Santos, Inácio Alves dos (2023)
This work presents a computational study, based on quantum calculations of electronic structure combined with calculations of the unimolecular velocity constant, of the reactions between anionic nucleophiles and alkyl nitrites in the gas phase. Alkyl nitrites have the most varied applications, such as: explosives, rocket propellants, vasodilators and intermediates in organic synthesis. Methyl nitrite is similar in structure and reactivity to methyl nitrate, a mechanism that has been well studied. Despite the usefulness of methyl nitrite, there is a lack of computational studies that describe its reactional behavior with ions in the gas phase. For this study, calculations based on the DFT were applied, with the functional B2PLYP-D3 and the basis function aug-cc pVDZ, and for refinement the method CCSD(T)/aug-cc-pVnZ n=(D,T) , in the steady states of the reaction between methyl nitrite and hydroxide ion, and between methyl nitrite and methoxide ion. Each stationary point of three competitive reaction pathways were characterized, namely: ECO2, elimination followed by dissociation, SN2@N and SN2@C, which corresponds to nucleophilic substitution at the nitrogen and carbon atom, respectively. From the obtained structures, the potential energy profile was constructed and the velocity constants determined by the RRKM method. For a visualization of the reaction dynamics, scan calculations were performed for the SN2@N and SN2@N mechanisms, and the potential energy surface was elaborated. For both reactions, the results indicate that ECO2 is favored by a lower activation barrier and rate constant, which differs from mass spectrometry results, where NO− is not detected. Thus, statistical methodology fails to predict the ECO2 path as the most favored, suggesting a dynamic behavior of the reaction between hydroxide ion and methyl nitrite. Despite this, the applied methodology manages to better describe the mechanisms of the reactions between the methoxide ion and the methyl nitrite, collaborating with the idea that complex nucleophiles reacting with methyl nitrites are better described, through static methods, than simple nucleophiles.